The Influence Of Bi Rate And Exchange Rate On Income From Profit Sharing (Case Study On Bank Mega Syariah) - Suwifania, Jihan; Nurwani, Nurwani; Sugianto, Sugianto (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This study aims to analyze the effect of BI Rate and exchange rate on profit sharing income. Profit sharing income is one of the main indicators of Islamic banking performance, which is influenced by various macroeconomic factors, including the benchmark interest rate (BI Rate) and the exchange rate. The method used in this study is quantitative with a multiple linear regression approach. The data used in this study are secondary data obtained from the official publication of Bank Indonesia, in the form of monthly BI Rate data, and the rupiah exchange rate against the US dollar, as well as monthly profit sharing income data from Bank Mega Syariah. The observation period in this study used data from January, March, May, July, September, and November, from 2020-2024, so that a total of 30 observation data were obtained. The results of the study indicate that the BI Rate has a positive effect on profit sharing income obtained from the results of the T test (sig. 0.000 0.05), while the T test of the exchange rate is 0.031 0.05, so that the exchange rate has a positive effect on profit sharing income. In addition, based on the F test, it is known that the sig. value. 0.000 0.05, then BI-Rate, and Exchange Rate together have a significant effect on Profit Sharing Income. This finding indicates that although Islamic banking does not use an interest system, changes in the BI Rate still affect customer investment preferences and market behavior. Therefore, strengthening risk management and diversifying financing portfolios are important in dealing with macroeconomic fluctuations.